Lisa Murphy on play : the foundation of children's learning - Murphy, Lisa, 1969- (St. Paul, MN : Redleaf Press, 2016)
Discover why playing is school readiness with this updated guide. Timely research and new stories highlight how play is vital to the social, physical, cognitive, and spiritual development of children. Learn the seven meaningful experiences we should provide children with every day and why they are so important.
Earlier edition published as: Play-- the foundation that supports the house of higher learning.
Includes bibliographical references (pages193 -194).
Keywords: Play; Early childhood education; Child development